Short‐Wave Infrared Synaptic Phototransistor with Ambient Light Adaptability for Flexible Artificial Night Visual System. (30th October 2022) - Huang, Xin; Liu, Yanwei; Liu, Guocai; Liu, Kai; Wei, Xiaofang; Zhu, Mingliang; Wen, Wei; Zhao, Zhiyuan; Guo, Yunlong; Liu, Yunqi
Abstract: Flexible organic monitoring system that can work in short‐wave infrared (SIR) region has great potential in autonomous driving, night driving safety, military encryption, biomedical imaging, and robot engineering. Especially, the development of infrared artificial vision system device that can autonomously improve the computing speed and adapt to different brightness ambient light is very important. However, it is a challenge for mimicking infrared visual adaptation because of the need for infrared absorbing materials and the need to control the concentration of carriers. In this study, inorganic quantum dot material is combined with organic materials to promote carrier separation and introduce interface defects that adjust the carrier concentration in transistors, which induce the synaptic behavior under SIR (1100 nm) light in darkness and the ability to adapt to white ambient light. Furthermore, the device array realizes the image recognition of SIR light at night with white ambient light of different brightness, exhibiting good self‐adaptability, and strong anti‐interference ability. These results demonstrate promising applications of the infrared synaptic phototransistors in adapted bionic optoelectronic devices. Abstract : PbS quantum dots are introduced in organic transistors to introduce defects that adjust the carrier concentration in the channel, realizing synaptic behavior under short‐wave infrared (SIR, 1100 nm) light. The device array realizes the image recognition of SIR light under white ambient light of different brightness, exhibiting good self‐adaptability and strong anti‐interference ability, promising in adapted bionic optoelectronic devices.